Religiosity and determinants of food consumption in urban and rural communities in Lampung Province - Habibi, Ahmad; Fachri, Adib; Utami, Pertiwi (Universitas Islam Indonesia, 2024)
IntroductionLampung Province consists of heterogeneous tribes and ethnicities. The majority is Muslim, followed by Protestants, Catholics, Hindus, and Buddhists. This makes Lampung Province known as the earth of ruwai jurai. This condition makes Lampung Province a miniature of the State of Indonesia.ObjectivesThis study investigates the religiosity and determinants of consumption of urban and sub-urban communities in Lampung Province.MethodThis study uses a quantitative research approach with a sample of 262 participants.ResultsThe findings revealed that there was no significant difference between rural and urban communities in purchasing food. Further, it was revealed that the respondents who made the object were consumers in the modern market with ages between 21-40 years old at 64.9% and with high school and Strata 1 education at 89.7%. Education level and age are the main factors in public consumption both in urban and rural areas. Based on the results of data analysis, it is known that the better understanding of religion a Muslim community has, the more selective they will be in purchasing the products they need. Therefore, it can be concluded that urban and rural communities consume research variables from the aspect of religiosity and economic determinants in the same condition so that modern markets as research locations provide an equal impact on urban and rural communities in consumption. ImplicationsStakeholders need to expand permits for the operation of modern markets by paying attention to the economy of traditional economic actors. Other factors, such as improving the quality and equitable distribution of education and increasing information about products both by producers and the government through mass media and social media, are also actively carried out carefully.Originality/Novelty This study provides an additional understanding of how religiosity contributes to consumption in societies with differing religious backgrounds.